Pharmacokinetics and in vitro effects of imipramine hydrochloride on the vas deferens in cattle - Bertschinger, H.J. (Hendrik Jan) (University of Pretoria, 2013)
Dissertation (MMedVet (Gyn))--University of Pretoria, 2005.